PERANCANGAN LOGO SEBAGAI IDENTITAS VISUAL STUDIO PROJECT.KITA DENGAN PENDEKATAN SEMIOTIKA PIERCE - Daka, Velsa Gloriana Adonae (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
When interpreting a logo as a company's face, it must reflect the company's vision and mission. When designed correctly, a simple logo can easily grab attention and change the audience's view of the brand. Project.KITA Studio builds branding through logos that reflect the identity of an architectural and interior design studio. The simplicity of the logo strongly conveys the company's condition and differentiates it from other architectural design studios in Kupang, East Nusa Tenggara. Using Charles Sanders Peirce's semiotic trichotomy approach, the logo was redesigned to be effective and efficient through its simplicity. The qualitative method used included interviews and data observation. This research produced a logo that aligns with project.KITA studio's identity, vision, and mission: to be a studio that prioritizes cooperation and comfortable communication and has a minimalist, modern design style. The simplicity of the logo containing the brand identity gives project.KITA studio a strong identity that is easier to remember.